2011
DOI: 10.1123/ijspp.6.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Energy System Contributions to the Special Judo Fitness Test

Abstract: Purpose:This study investigated the energy system contributions of judo athletes to the Special Judo Fitness Test (SJFT).Methods:Fourteen male judo athletes performed the SJFT, which comprised three periods of judo activity (A = 15 s, B and C = 30 s) interspersed with 10 s rest intervals. During this test, one athlete threw two others positioned 6 m from each other using the ippon-seoi-nage technique. The fractions of the aerobic, anaerobic alactic and anaerobic lactic systems were calculated based on oxygen u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 19 publications
(27 reference statements)
4
88
0
11
Order By: Relevance
“…The higher alactic contribution, according to the authors, seems to be a consequence of the high-intensity efforts performed during the test and of its intermittent nature, characteristics also reported in previous studies involving intermittent exercises [11][12][13][14] . The analysis of blood lactate concentrations after the SJFT and of oxygen uptake during the test shows similarities of these variables to thoseobtained during combats 31 . This points out that the SJFT is able to induce glycolytic and oxidative demands similar to those of a judo combat.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The higher alactic contribution, according to the authors, seems to be a consequence of the high-intensity efforts performed during the test and of its intermittent nature, characteristics also reported in previous studies involving intermittent exercises [11][12][13][14] . The analysis of blood lactate concentrations after the SJFT and of oxygen uptake during the test shows similarities of these variables to thoseobtained during combats 31 . This points out that the SJFT is able to induce glycolytic and oxidative demands similar to those of a judo combat.…”
Section: Discussionsupporting
confidence: 60%
“…As for the energetic cost involved in the test, Franchini et al 31 observed greater alactic anaerobic participation (42.3%), followed by anaerobic lactic (29.5%) and oxidative (28.2%) contribution, the last two of which with no statistical difference. The higher alactic contribution, according to the authors, seems to be a consequence of the high-intensity efforts performed during the test and of its intermittent nature, characteristics also reported in previous studies involving intermittent exercises [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 95%
“…Resultado semelhante foi observado em estudo em que judocas (n = 12) realizaram quatro combates, onde as concentrações de lactato pós-luta do último combate (14,6 ± 3.6 mmol/L) foram inferiores àquelas concentrações sanguíneas observadas nas primeira (18,1 ± 4,4 mmol/L) e segunda (17,0 ± 3,6 mmol/L) simulações (BONITCH-GÓNGORA et al, 2012). Bonitch-Domínguez et al Além disso, quando analisada a contribuição dos sistemas em ações específicas de judô e taekwondo, evidencia-se grande participação do sistema oxidativo apesar das elevadas [LAC] (CAMPOS et al, 2012;FRANCHINI et al, 2011c).…”
Section: Estudo 1 -Luta Fragmentadaunclassified
“…No judô, atletas realizaram um teste específico de curta duração -Special Judo Fitness Test -, no qual os avaliados realizam o máximo de projeções de um golpe específico (ippon seoi-nage) em três blocos (1 bloco de 15 s e 2 blocos de 30 s) intercalados por 10 s. Nessas avaliações foi descrito que a contribuição energética foi de 42 ± 6% do sistema alático, 30 ± 6 do sistema lático e 28 ± do sistema aeróbio (FRANCHINI et al, 2011c). Embora nesse teste a contribuição aeróbia tenha sido a menor entre os três sistemas ela foi significativa, além disso, deve-se lembrar que tem sido demonstrado que com o aumento da duração da atividade aumenta-se concomitantemente a participação das vias aeróbias de fornecimento de energia (GAITANOS et al, 1993).…”
Section: Estudo 1 -Luta Fragmentadaunclassified
See 1 more Smart Citation